Size effects of nana-to-micro particles of cBN coated with tin matrix on WC substrate for hard turning applications - Nakkiew,W. (Chiang Mai University, 2015)
An innovative two-stage composite coating method, which comprises of Electrostatic Spray Coating (ESC) and Chemical Vapor Infiltration (CVI) has been developed by the University of Arkansas and NanoMech, LLC for coating cutting tools in hard turning. For a coated cBN-TiN composite tool, ESC of nano-to-micron cBN particles is sprayed on WC substrate to create a porous matrix, and then CVI is used to infiltrate TiN through this cBN porous matrix to form a very dense coating. Two sizes of cBN particles (cBN particle < 0.5 μm and cBN particle < 2 μm) are used in this paper for investigating effects of coated particle sizes on cutting performances and microstructures of the coating layers. Since tool life is one of several criteria for evaluating cutting tool's performances, tool life studies of tools with two different coated cBN particle sizes are performed. The results show that a coated cutting tool with a smaller coated cBN particle size has a comparative tool life as solid Polycrystalline Boron Nitride (PCBN) tool which is a dominant tool in hard turning applications and the tool life twice as long as a coated tools with larger cBN particle size. Microstructures of coated layers for the tool with smaller cBN particle size at the flank location show a more uniform coating than the coated tool with larger cBN size. A regression analysis model for the tool life of coated composite tools with cBN particle size less than 0.5 μm is constructed as a demonstration for a mean to predict a tool life of cutting tool in metal cutting.